Development of a rabbit's urethral sphincter deficiency animal model for anatomical-functional evaluation - Skaff, M.; Pinto, E. R.S.; Leite, K. R.M.; Almeida, F. G. (FapUNIFESP (SciELO), 2012)
Objective: The aim of the study was to develop a new durable animal model (using rabbits) for anatomical-functional evaluation of urethral sphincter deficiency. Materials and Methods: A total of 40 new Zealand male rabbits, weighting 2.500 kg to 3.100 kg, were evaluated to develop an incontinent animal model. Thirty-two animals underwent urethrolysis and 8 animals received sham operation. Before and at 2, 4, 8 and 12 weeks after urethrolysis or sham operation, it was performed cystometry and leak point pressure (LPP) evaluation with different bladder distension volumes (10, 20, 30 mL). In each time point, 10 animals (8 from the study group and 2 from the sham group) were sacrificed to harvest the bladder and urethra. The samples were evaluated by H & E and Masson's Trichrome to determine urethral morphology and collagen/smooth muscle density. Results: Twelve weeks after urethrolysis, it was observed a significant decrease in LPP regardless the bladder volume (from 33.7 ± 6.6 to 12.8 ± 2.2 cmH2O). The histological analysis evidenced a decrease of 22% in smooth muscle density with a proportional increase in the collagen, vessels and elastin density (p < 0.01). Conclusions: Transabdominal urethrolysis develops urethral sphincter insufficiency in rabbits, with significant decrease in LPP associated with decrease of smooth muscle fibers and increase of collagen density. This animal model can be used to test autologous cell therapy for stress urinary incontinence treatment.
Keywords: Animal model; Stem cells; Tissue engineering; Transabdominal urethrolysis; Urethral sphincter deficiency; Urinary incontinence